2010
DOI: 10.1063/1.3385427
|View full text |Cite
|
Sign up to set email alerts
|

Shear-mode piezoelectric properties of ternary Pb(In1/2Nb1/2)O3–Pb(Mg1/3Nb2/3)O3–PbTiO3 single crystals

Abstract: A systematic study of the optimized orientation and temperature dependence of shear-mode piezoelectric properties for ternary Pb͑In 1/2 Nb 1/2 ͒O 3 -Pb͑Mg 1/3 Nb 2/3 ͒O 3 -PbTiO 3 ͑PIN-PMN-PT or PIMNT͒ piezocrystals was carried out. It was found that ͓111͔-poled samples presented the best shear piezoelectric properties when driving along ͓110͔ ͑the thickness direction͒. The electromechanical coupling coefficient k 15 and piezoelectric coefficient d 15 and g 15 were found to be 96.4%, 5966 pC/N, and 0.047 Vm/N,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Recently, various properties of PIN-PMN-PT single crystals near MPB including elastic, dielectric, and piezoelectric properties have been studied under different poling conditions. [9][10][11][12][13][14][15][16][17][18][19][20][21] However, the ferroelectric phase transition behaviors of PIN-PMN-PT single crystals have not been studied in detail. A great portion of the published data on this system are reported on poled samples at room temperatures, and studies on the phase transition behaviors in the temperature window of as-grown or unpoled samples in comparison with poled ones are scarce.…”
mentioning
confidence: 99%
“…Recently, various properties of PIN-PMN-PT single crystals near MPB including elastic, dielectric, and piezoelectric properties have been studied under different poling conditions. [9][10][11][12][13][14][15][16][17][18][19][20][21] However, the ferroelectric phase transition behaviors of PIN-PMN-PT single crystals have not been studied in detail. A great portion of the published data on this system are reported on poled samples at room temperatures, and studies on the phase transition behaviors in the temperature window of as-grown or unpoled samples in comparison with poled ones are scarce.…”
mentioning
confidence: 99%
“…Recently, the melt Bridgman growth of xPb(In 1/2 Nb 1/2 ) O 3 -yPb(Mg 1/3 Nb 2/3 )O 3 -(1À xÀy)PbTiO 3 {PIMNT [100x/100y/100 (1À xÀy)]} ternary single crystals with large size and high quality have been reported, showing broadened temperature usage range (T RT 4100 1C) and comparable piezoelectric properties to those of PMNT crystals [9,10]. Furthermore, Yu et al [11] recently found that tetragonal PIMNT (41/17/42) ternary single crystals have relatively high T C of 253 1C compared with that of PMNT (62/38) crystals.…”
Section: Introductionmentioning
confidence: 96%
“…[9][10][11][12][13][14] Yet, strain under high electric field was seldom studied systematically. In strain actuator design, it is important for the material to exhibit high strain values with low nonlinear hysteresis, which determines the actuator performance.…”
mentioning
confidence: 99%